The Classification and Evolution of Bacterial Cross-Feeding - Smith, Nick W.; Shorten, Paul R.; Altermann, Eric; Roy, Nicole C.; McNabb, Warren C. (Frontiers in Ecology and Evolution, 2019)
Bacterial feeding has evolved towards specific evolutionary niches and the sources of energy differ between species and strains. Although bacteria fundamentally compete for nutrients, the excreted products from one strain may be the preferred energy source or a source of essential nutrients for another strain. The large variability in feeding preferences between bacterial strains often provides for complex cross-feeding relationships between bacteria, particularly in complex environments such as the human lower gut, which impacts on the host’s digestion and nutrition. Although a large amount of information is available on cross-feeding between bacterial strains, it is important to consider the evolution of cross-feeding. Adaptation to environmental stimuli is a continuous process, thus understanding the evolution of microbial cross-feeding interactions allows us to determine the resilience of microbial populations to changes to this environment, such as changes in nutrient supply, and how new interactions might emerge in the future. In this review, we provide a framework of terminology dividing bacterial cross-feeding into four forms that can be used for the classification and analysis of cross-feeding dynamics. Under the proposed framework, we discuss the evolutionary origins for the four forms of cross-feeding and factors such as spatial structure that influence their emergence and subsequent persistence. This review draws from both the theoretical and experimental evolutionary literature to provide a cross-disciplinary perspective on the evolution of different types of cross-feeding.